IMPLEMENTASI TEORI-TEORI BELAJAR DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Muna Hatija (STAI Sangatta Kutai Timur, 2023)
This study aims to find the concepts and types of learning theory, describe the application of learning theory in PAI learning, and analyze the advantages and disadvantages of learning theory in PAI learning. The method applied in this study is a qualitative research method with a type of literature review. The result of this study is the concept of learning theory’s' was a theory that is used in the learning process in the classroom and outside the classroom that begins with designing the proper method. Various learning theories are Behavioristic, Cognitive, Constructivist, and Humanistic. Its application in PAI learning is that behavioristic theory makes it easier for educators and students in learning process. The cognitive theory implementation in PAI learning can also manifest noble character in students by adhering to the base sources of Islamic teachings. The application of constructivist theory in learning can be done through the five senses, experience, and the environment that will give birth to new knowledge constructions. At the same time, this humanistic theory can be used as a role model in PAI learning to humanize humans. Every theory applied in the PAI learning process certainly has advantages and disadvantages. The advantages and disadvantages of each approach in its application in PAI learning allow an educator to use all theories in a lesson, its goal is to complement one theory with other.